Preference and willingness to pay for meat substitutes based on micro-algae. (1st November 2019) - Weinrich, Ramona; Elshiewy, Ossama
Abstract: Current meat consumption and production patterns are far from sustainable and place a heavy burden on the environment. Excessive meat consumption is also considered detrimental to consumer health. Hence, more consumers are willing to opt for meat substitutes to counteract these downsides of excessive meat consumption. However, in many Western countries, market shares for meat substitutes still have to increase significantly if they are to support responsible consumption and production. Consequently, more research is needed to take a closer look at consumer preferences for meat substitutes. This study aims to fill this research gap by analyzing consumer preferences for meat substitutes based on micro-algae. First, a choice-based conjoint analysis was conducted in three Western European countries (Germany, Netherlands, France) to reveal consumer preferences and willingness to pay for meat substitutes based on micro-algae. Second, a multi-item scale was developed to measure consumer attitudes toward meat and meat substitutes. Third, these results were combined to obtain novel insights about attitudinal drivers of consumer preference and willingness to pay for meat substitutes based on micro-algae. In summary, findings from this study provide important insights for food engineers, food marketers, and policy makers when it comes to product development and increasing market shares for meat substitutes based on micro-algae.